Vegetative growth of seedlings of arabic coffee (Coffea arabica L.) submitted to different levels of shade - Tatagiba, Sandro Dan; Pezzopane, José Eduardo Macedo; dos Reis, Edvaldo Fialho (Coffee Science - ISSN 1984-3909, 2011)
The production of coffee seedlings under sunlight is a technique used by some producers in nursery. Results and uses are based, in most cases, for comments and there is a need for scientific studies that can show the real importance of the method. Thus, it is suggested in this work to study the growth and production of seedlings of (Coffea arabica L.) kept under full sunlight and under different levels of shade. The experiment was installed in the scheme of a randomized design in split plot in time (40, 80 and 120 days), using 12 replicates for the characteristics of diameter of the stem and height, and three replicates for foliate area, relation root/aerial part, aerial part dry matter, root and total. The treatments consisted of the following levels of shading: 0% shade, or the seedlings were kept in full sunlight, 22%, 50% and 88% shading. According to the results of growth traits analyzed, the seedlings grew better at 22 and 50% shading, with higher vegetative growth in relation to maintained in full sunlight to shade and 88%, allowing the formation of more vigorous seedlings, verified mainly by the total dry matter of plants. There was a trend of increasing height and leaf area with increasing shading, while the stem diameter was reduced by 88% shading.